Anxiety sensitivity and nonmedical benzodiazepine use among adults with opioid use disorder. (February 2017) - McHugh, R. Kathryn; Votaw, Victoria R.; Bogunovic, Olivera; Karakula, Sterling L.; Griffin, Margaret L.; Weiss, Roger D.
Abstract: Nonmedical benzodiazepine use is common among adults with opioid use disorder; however, little is known about this co-occurrence. Anxiety sensitivity–the fear of anxiety symptoms and sensations–motivates behaviors to escape and avoid distressing states, and accordingly is associated with coping motives for substance use. This might be particularly relevant among women, who report using substances to cope with negative emotions more often than men. The aim of the current study was to examine whether nonmedical benzodiazepine use was associated with higher anxiety sensitivity among treatment-seeking adults diagnosed with opioid use disorder, and to investigate whether gender moderated this association. A sample of adults (ranging in age from 18 to 81 years) receiving inpatient treatment for opioid use disorder ( N = 257) completed measures of anxiety, anxiety sensitivity, and benzodiazepine use frequency. Results of an analysis of variance indicated that frequency of past-month nonmedical benzodiazepine use was associated with significantly higher anxiety sensitivity. This effect remained when controlling for the effect of anxiety symptoms ( F [1, 251] = 3.91, p = 0.049, η p 2 = 0.02). Gender moderated this association, and post-hoc analyses found a strong association between nonmedical benzodiazepine use and anxiety sensitivity in women, and not men. Anxiety sensitivity, which can be reduced with treatment, might be a candidate therapeutic target in this population, particularly in women. Highlights: Benzodiazepine abuse is common among those with opioid use disorder. Our sample consisted of adults receiving treatment for opioid use disorder. Frequent past-month benzodiazepine abuse was associated with high anxiety sensitivity. The link between benzodiazepine abuse and anxiety sensitivity was unique to women. Women may be particularly susceptible to abusing benzodiazepines to manage anxiety.